Pengukuran Program Gamasya (Bantuan Modal dan Gerobak) di LAZIS Nurul Falah Surabaya Menggunakan Indeks Pendayagunaan Zakat (IPZ) - Choiriya Rosita Anatasya; Fadilatus Sa’diyah; Achmad Dzulkifli; Firman Ramadhan; Hamam Nashiruddin Afandi; Moh. Al-Farizi; Saifullah Nurdin (P3M Politeknik Negeri Banjarmasin, 2025)
LAZIS Nurul Falah Surabaya is an Islamic philanthropic institution that manages zakat, infaq, and sadaqah funds professionally to empower the community’s economy. One of its flagship initiatives is the Gamasya (Gerobak Mandiri Sejahtera) program, which provides business capital and food carts to mustahik (zakat recipients) with the aim of fostering economic independence. This study aims to measure the outcomes of the Gamasya Program using the Zakat Utilization Index (IPZ) developed by Puskas BAZNAS. A descriptive quantitative approach was applied by distributing questionnaires and conducting interviews with 15 mustahik who received assistance. The results show an IPZ score categorized as “good.” The highest dimension was da’wah, followed by economic, environmental, cultural, and social. These findings indicate that the Gamasya Program has contributed positively to improving income levels, entrepreneurial behavior, spiritual values, and environmental awareness among mustahik. Therefore, it is recommended that LAZIS Nurul Falah strengthen business mentoring, entrepreneurship training, and strategic partnerships to help mustahik achieve full independence and eventually transform into muzakki (zakat givers) in the future.